Is “Al Ghodad Al- Somm” as an Arabic translation for Endocrinology deficient and needs to be revisited?: Results of Survey of physicians’ perceptions - Afandi, Bachar Omar; Beshyah, Salem; Saadi, Hussein Fadel; Al- Saleh, Yousef; Hatahet, Mohamed Hasan (Journal of medical and pharmaceutical sciences, 2020)
Objectives: “Al Ghodad Al- Somm” is an old Arabic translation for the field of Endocrinology which doesn’t accurately reflect the Greek terminology “Endocrine”, and doesn’t fully describe this science of the glands that secrete hormones and their disorders. Our objectives were to seek the opinion of Arab physicians (Endocrinologists and other physicians) about the accuracy and applicability of the Arabic translation and to suggest a better descriptive and reflective name for the specialty. Methods: An electronic survey of various Arab physicians from the Gulf, Fertile Crescent and North Africa. Results: Responses of 383 out of 400 participants were valid for analysis. The survey results showed that (49%) of participating endocrinologists and (34%) of physicians from other specialties expressed that a more accurate Arabic translation is needed. Conclusions: Practicing Arab physicians expressed the opinion that the Arabic translation “Al- Somm” is deficient and a more accurate term is needed to better reflect our current knowledge of this science of the glands that secrete hormones and their disorders. “The science of hormonal glands, diabetes and metabolism" has been proposed as a term that may better serve this purpose.